2011
DOI: 10.1093/arclin/acr084
|View full text |Cite
|
Sign up to set email alerts
|

Are Embedded Validity Indices Equivalent to Free-Standing Symptom Validity Tests?

Abstract: Symptom validity assessment is an important part of neuropsychological evaluation. There are currently several free-standing symptom validity tests (SVTs), as well as a number of empirically derived embedded validity indices, that have been developed to assess that an examinee is putting forth an optimal level of effort during testing. The use of embedded validity indices is attractive since they do not increase overall testing time and may also be less vulnerable to coaching. In addition, there are some insta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(22 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…The results showed that Western European neuropsychologists exhib-ited an awareness of the occurrence of non-credible symptom reports in both forensic and clinical assessments. The general estimate of the prevalence of malingering (10% in clinical assessments and 20% in forensic assessments) corresponded broadly to the data from empirical studies (e.g., Kemp et al, 2008;Gervais et al, 2004;Miele et al, 2012;Boone, 2013), although the estimate found in forensic studies was at the lower end of the range found in empirical studies.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The results showed that Western European neuropsychologists exhib-ited an awareness of the occurrence of non-credible symptom reports in both forensic and clinical assessments. The general estimate of the prevalence of malingering (10% in clinical assessments and 20% in forensic assessments) corresponded broadly to the data from empirical studies (e.g., Kemp et al, 2008;Gervais et al, 2004;Miele et al, 2012;Boone, 2013), although the estimate found in forensic studies was at the lower end of the range found in empirical studies.…”
Section: Discussionsupporting
confidence: 67%
“…Another striking finding is that less than one of every four respondents stated that they often or always used embedded indicators to determine the validity of the ob-tained test scores. Although research shows that embedded measures are often less sensitive than stand-alone SVTs for the detection of underperformance (e.g., Miele et al, 2012), acceptable sensitivity and specificity rates (84% and 94%, respectively) have been found by Victor, Boone, Serpa, Buehler, and Ziegler (2009) when using a "two-failure rule" (any pairwise failure of two embedded indicators of underperfor-mance). Moreover, embedded measures have certain advantages over stand-alone SVTs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Embedded performance validity tests (PVTs) derived from commonly administered neuropsychological measures serve "double duty" in that they function as measures of both neurocognitive ability and noncredible performance Whiteside, Wald, & Busse, 2011). They are helpful in the detection of noncredible performance for reasons of increased costeffectiveness and efficiency by making use of extant materials and added resistance to coaching and detection by examinees (Brennan et al, 2009;Heilbronner et al, 2009;Miele, Gunner, Lynch, & McCaffrey, 2011). Embedded PVTs commonly utilize forced-choice or other memory-related paradigms (Bouman, Hendriks, Schmand, Kessels, & Aldenkamp, 2016;King, Gfeller, & Davis, 1998;Olsen, Schroeder, Heinrichs, & Martin, 2019;Schwartz et al, 2016).…”
mentioning
confidence: 99%
“…This approach is a less obvious method of assessing suboptimal effort and is thought to be less susceptible to coaching (Heilbronner et al, 2009). However, embedded measures have also been shown to have higher misclassification rates than standalone PVTs (Miele, Gunner, Lynch, & McCaffrey, 2012).…”
mentioning
confidence: 99%